DEVELOPMENT OF SALES INFORMATION SYSTEM FOR SME WITH THE WATERFALL METHOD: A GROCERY STORE BSR CASE - Santo Wijaya; Andhika Andhika; Muhammad Ilyas (Jurnal Teknik Informatika (Jutif), 2022)
Grocery store BSR is an SME engaged in the sale of goods for basic daily needs. Today's business processes are still done manually. It has in-store sales services and a mobile sales team to reach a wider rural area in Central Java province of Indonesia. The competition in the grocery store SME business is tighter and increasingly competitive, so shop owners consider increasing the efficiency of business processes by creating web and mobile android of sales information system applications, which are the objectives of this study. We use the waterfall method to develop the sales information system. The development of A web application for in-store use and an android mobile application for mobile sales teams. From the business process analysis, three processes can be streamlined with the use of this application. Also, another uniqueness is the minimum and maximum selling price feature for each sales item to give the sales team flexibility in determining the selling price to the customers. User acceptance test has been carried out by the research team with black-box method as per use-case diagram with the shop owner. The testing results showed that the developed information system increase the process business efficiency in the grocery store BSR. Hence, the objective to develop sales information system has been achieved.